1998
DOI: 10.1046/j.1365-3148.1998.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Decay‐accelerating factor (CD55) deficiency phenotypes in Japanese

Abstract: Decay‐accelerating factor (DAF, CD55) is a complement regulatory glycoprotein that expresses the Cromer‐system blood group antigens. Two, very rare, inherited DAF‐deficiency phenotypes, Inab and Dr(a–), were identified in Japanese propositi. Red cells of the Inab phenotype propositus had no Cromer‐system antigens and did not bind monoclonal anti‐DAF. The Inab propositus was homozygous for a DAF non‐sense mutation, converting the Trp53 codon to a stop codon; her parents were heterozygous for this mutation. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…Interestingly, however, it has been reported that DAF (CD55) deletion, also known as the Inab phenotype, hardly alters the sensitivity of cells to lysis by complement and only with inhibition of CD59 does hemolysis occur in vitro [3134]. Deficient expression of the complement regulatory proteins CD55 and CD59 has been found in a variety of human diseases (Table 1) [35–61], however, most prevalently in autoimmune hemocytopenia, autoimmune vasculitis, and other diseases involving dysregulated immune responses [41, 44, 6268].…”
Section: Daf In Human Autoimmune Diseasesmentioning
confidence: 99%
“…Interestingly, however, it has been reported that DAF (CD55) deletion, also known as the Inab phenotype, hardly alters the sensitivity of cells to lysis by complement and only with inhibition of CD59 does hemolysis occur in vitro [3134]. Deficient expression of the complement regulatory proteins CD55 and CD59 has been found in a variety of human diseases (Table 1) [35–61], however, most prevalently in autoimmune hemocytopenia, autoimmune vasculitis, and other diseases involving dysregulated immune responses [41, 44, 6268].…”
Section: Daf In Human Autoimmune Diseasesmentioning
confidence: 99%
“…Furthermore, the remaining antigen, IFC (antibodies to which are produced by individuals of the Inab phenotype), is composed of sites in multiple SCR domains of DAF, as demonstrated by the inhibition of hemagglutination with soluble recombinant domain-deletion mutants of DAF. 18,23 This molecular composition is expected for the antibody response of individu- als who lack expression of DAF. Two separate mutations have been described in the Inab phenotype, and these are also listed in Table 1.…”
Section: Discussionmentioning
confidence: 94%
“…These results describe the molecular basis of 9 of the 10 assigned antigens of the Cromer blood group system. Furthermore, the remaining antigen, IFC (antibodies to which are produced by individuals of the Inab phenotype), is composed of sites in multiple SCR domains of DAF, as demonstrated by the inhibition of hemagglutination with soluble recombinant domain‐deletion mutants of DAF 18,23 . This molecular composition is expected for the antibody response of individuals who lack expression of DAF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations